Measurement of betamethasone concentration in maternal serum treated for fetal lung maturity; Is it feasible?. Issue 1 (December 2016) - Salim, Raed; Suleiman, Abeer; Colodner, Raul; Nachum, Zohar; Goldstein, Lee; Shalev, Eliezer
Abstract Background The association between maternal serum concentration of betamethasone given for fetal lung maturity and perinatal outcome has not been investigated. This may be due to an absence of a reliable method for measuring serum betamethasone concentrations. We aimed in the current study to assess the feasibility of a specific ELISA kit to measure the concentrations of betamethasone in maternal serum and to examine the trend of sequential measurements after a course of betamethasone for fetal lung maturity. Methods Pregnant women at risk for preterm birth who received betamethasone between 24 and 34 weeks of gestation were prospectively included. Serum concentrations were determined before administering betamethasone (baseline), and 36 hours, 48 hours, 72 hours, and 5 to 7 days after the 1st dose. Betamethasone concentration in samples was determined using Corticosteroid ELISA kit. The Friedman test was used to test whether there were significant differences between the measurements. Results Five singleton pregnancies were included. Using the ELISA kit, betamethasone concentration in maternal serum samples was obtained for all women. Among the five measurements performed, the concentration was highest at 36 hours after the 1st dose and close to baseline at the 5th measurement performed after 5 to 7 days (p  < 0.05). Serum concentration varied at each time point between the five women but similar trend was observed. Conclusion Betamethasone concentration is measurable in the serum of pregnant women with this ELISA kit.